Methods to integrate overland, ephemeral gully and streambank erosion models - Modala, Naga Raghuveer (Kansas State University, 2010)
Sediment is considered as one of the important pollutant of concern in the U.S. In order to develop watershed management plans that address sediment pollution, it is essential to identify all sources of sediment in a watershed. The overall goal of this research is to quantify the total sediment from a watershed by integrating the outputs of three types of sediment sources: sheet and rill erosion, ephemeral gully erosion, and streambank erosion, that each operates at different spatial and temporal scales. This approach will be demonstrated in Black Vermillion River Watershed using AnnAGNPS (overland flow/erosion model), REGEM (ephemeral gully erosion model) and field measured values of streambank erosion. The study area includes three subwatersheds (Irish Creek, the Black Vermillion River Main Stem, and North Fork of the Black Vermillion), each monitored for continuous stream flow, base flow and event-based suspended sediment subwatershed export, annual streambank erosion, for 2 years. NASS land use, SSURGO soils data, 30-m DEMs, and local weather data were used to generate input data needed by the models. Stream monitoring data were used to calibrate the models. This paper will present results from independently calibrated and validated combinations of AnnAGNPS, REGEM, and filed measured streambank erosion. Our hypothesis is that use of separate models to simulate sediment load contributions for each sediment source will improve model agreement with measured watershed sediment yield data.
Keywords: Watershed Modeling; Engineering, Environmental (0775)